2018
DOI: 10.1002/ajpa.23601
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral asymmetry of the humerus in Neandertals, Australian aborigines and medieval humans

Abstract: High levels of directional asymmetry of cross-sectional shape and properties in medieval farmers may be caused by the performance of more physically demanding tasks using one side of the body from an early age in that population. Various patterns of asymmetry in Neandertals and modern humans may be caused by different habitual behaviors during growth, eco-geographic patterns in body proportions, genetic factors, and differences in ontogeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 89 publications
(128 reference statements)
2
24
0
Order By: Relevance
“…Moreover, scaling to bone length provides greater compatibility between the results obtained in this study, and those found in the literature [1,42,52,56]. Ratios of principal moments of area (Imax/Imin) and relative cortical area (%CA) were not standardized either to humeral length or to body mass [42,57]. The anatomical traits quantified on the endocast and the humeri are of different natures.…”
Section: Methodssupporting
confidence: 56%
See 3 more Smart Citations
“…Moreover, scaling to bone length provides greater compatibility between the results obtained in this study, and those found in the literature [1,42,52,56]. Ratios of principal moments of area (Imax/Imin) and relative cortical area (%CA) were not standardized either to humeral length or to body mass [42,57]. The anatomical traits quantified on the endocast and the humeri are of different natures.…”
Section: Methodssupporting
confidence: 56%
“…Moreover, this biomechanical property is very variable within human populations and can express phylogenetic information [68], which is why interpretations of DA Imax/Imin on a small sample size should be drawn with caution. Previous research on the same sample showed that this medieval population was characterized by significant and more pronounced DA of all biomechanical properties (%CA, J and Imax/Imin) than Neandertals and recent Aboriginal Australians [42]. The discrepancy between these results is probably a consequence of analyzing leftand right-handed individuals separately in the last research.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, the sacrum does not have a long period in which it may be sensitive to lateralized habitual behavior or loading. However, Neandertals and Late Pleistocene humans exhibited stronger asymmetry in the upper limbs than do the majority of extant humans (Sparacello, Villotte, Shackelford, & Trinkaus, ; Trinkaus, Churchill, & Ruff, , but see Kubicka, Nowaczewska, Balzeau, & Piontek, ). There is no evidence of similarly strong compensatory asymmetry in the lower body (Ruff, Trinkaus, Walker, & Larsen, ; Trinkaus et al, ), which given the small number of Neandertal sacra preserved, prevents any assumptions about sacral asymmetry in Neandertals.…”
Section: Discussionmentioning
confidence: 99%